Association of left ventricular hypertrophy and functional impairment with cardiovascular outcomes and mortality among patients with chronic kidney disease, results from the C‐STRIDE study. Issue 4 (15th December 2021) - Wang, Jinwei; Lv, Jicheng; He, Kevin; Wang, Fang; Gao, Bixia; Zhao, Ming‐Hui; Zhang, Luxia; ,
Abstract: Aim: Left ventricular hypertrophy and impaired systolic and diastolic function are commonly seen in patients with chronic kidney disease (CKD), but relationships between the disorders and cardiovascular outcomes are not well established among the patients. Methods: Totally, 2020 patients with CKD Stages 1–4 were used in the analysis. Left ventricular hypertrophy was defined by left ventricular mass index >49.2 g/m 2.7 in men and > 46.7 g/m 2.7 in women. Incident heart failure, non‐heart failure cardiovascular events, and all‐cause mortality were recorded longitudinally. Cox proportional hazards regression model was used to evaluate the association between the echo parameters and the outcomes, with death treated as the competing risk event for the cardiovascular events. Results: After a median follow‐up of 4.5 years, 53 heart failure, 76 non‐heart failure cardiovascular events and 82 deaths occurred. No overall association was found between left ventricular hypertrophy and subsequent heart failure, but the relationship was significant among patients with no diabetes with the multivariable adjusted hazard ratio of 3.66 (95% confidence interval: 1.42–9.46). Ejection fraction<55% was associated with both heart failure and non‐heart failure cardiovascular events with hazard ratios of 3.16 (1.28–7.77) and 2.76 (1.08–7.04), respectively. E/A ratio ≤ 0.75 was associated with non‐heart failure cardiovascular events [hazard ratio = 2.03 (1.09–3.80)], compared with E/A ratio of 0.76–1.49. Conclusion: Associations of reduced left ventricular ejection fraction with both heart failure and non‐heart failure cardiovascular events and of impaired left ventricular diastolic function with non‐heart failure cardiovascular events were validated in a Chinese cohort of CKD. SUMMARY AT A GLANCE: This is a multi‐centre cohort from China on the association of left ventricular hypertrophy and functional impairment with cardiovascular outcomes and mortality in CKD patients. Ejection fraction <55% was associated with both heart failure and non‐heart failure cardiovascular events.